SOSIALISASI DAN PELATIHAN PENULISAN ARTIKEL ILMIAH UNTUK MENGEMBANGKAN KEMAMPUAN GURU IPA DI SMP NEGERI 15 KOTA BENGKULU - Rosane Medriati; Desi Hanisa Putri; Dedi Hamdani (DHARMA RAFLESIA, 2017)
This public service aims to disseminate activity in writing scientific articles to develop the theoretical scientific capacities, to train skill of science teachers for popular sciencewriting in an efficient and effective way to gain recognition as a professional teacher (c)The creation of a post made by a teacher who can be recognized scientifically and beaccountable. The public service is implemented in the Junior High School 15, City ofBengkulu. Participants consist of all teachers of Mathematics and Science, the principaland all vice principals. The method forms of this public service are (1) Dissemination ofarticle writing (technical writing scientific articles, non-research article writing, articlewriting national, international article writing), (2) Training in writing research article.The result shows that the teachers begin to understand and know how to write a researcharticle, and able to make the article from the results of studies that have been done.Keyword: teachers, training, mentoring, scientific articles